Migrants’ Transactions: a Way of Economic Growth? - A. A. Mamatkhanov (Plekhanov Russian University of Economics, 2020)
The growing number of international migrants plays an important role in the life of host and home countries by affecting their economy, society and population. A special place in processes of population migration is taken by cash transactions of migrants living abroad. In line with certain positive effects of migrants and migrants’ transactions there are negative, latent factors that have not been studied yet. Some researchers point to such adverse effect as a rise in unemployment among the population of the home country, as members of households with migrants, when they start getting a stable income from abroad lose incentive to economic activity and acquire the dependence mood. The author discusses the most important negative effect, i.e. excessive dependence of the country on the inflow of migrants’ cash transactions, which could result in ‘dollarization’ of country economy and even in symptoms of the ‘Holland disease’. The article shows that in Uzbekistan the net – sender of labour migrants, the impact of the migration process and migrants’ transactions on economy and customer behavior of the population are extremely topical. By investigating the mentioned problems it is necessary to design integral state policy in the field of labour migration.